Prophage Induction of Noninducible Coliphage 186 - Woods, Walter H. (1974)
Coliphage 186 has been regarded as a member of the noninducible group of coliphages. Evidence that prophage 186 is induced by ultraviolet irradiation or by treatment with nalidixic acid or mitomycin C is now presented. The phage yields were similar to those from lysogens of the inducible phage lambda, and the induction required a recA(+) host. A noninducible mutant of 186 was isolated from its heat-inducible derivative, 186cIts, that was no longer inducible by ultraviolet irradiation but remained heat inducible. That zygotic induction of 186 after transfer from a lysogenic male to a non-lysogenic recipient did not occur is indicated by the following findings: (i) there was only a slight increase in phage titer; (ii) similar levels of recombinants were obtained for markers adjacent or distal to the phage integration site, whether the recipient was lysogenic or not, and there was no effect on the gradient of marker transfer; (iii) lysogenic recombinants were readily found and the co-transfer of 186 with adjacent markers was the same to lysogenic or non-lysogenic recipients. Thus, 186 formed an inducible prophage that did not display zygotic induction. Nevertheless, it shared many properties with the noninducible phage P2 as outlined in the discussion.